Analisis Cost-Consequences Terapi Penyakit Pneumonia Di Rumah Sakit Umum Daerah Praya, Nusa Tenggara Barat - Lila Wahyuni; Oktri Lestari; Elza Rachman Panca Priyanda; Riri Amanda Fitriani (Syntax Corporation Indonesia, 2022)
Pneumonia is an infection of lower respiratory tract caused by bacteria, viruses or fungi and a major cause of problem health in both developing and developed countries. Antibiotics are the first line therapy pneumonia caused by bacteria. Rational antibiotic therapy in the treatment of pneumonia is an important reason the need for pharmacoeconomic analysis. This study aimed to describe the cost of picture pneumonia treatment, the proportion of cost components, drug/drug combination that has the optimal effectiveness and the lowest cost. This research was descriptive non experimental research with retrospective data collection with method cost consequences analysis. Data taken were patient data with primary diagnoses of hospitalized pneumonia and according to inclusion and exclusion criteria. The results showed 57 patients met inclusion and exclusion criteria. Pneumonia patients are predominantly 0-18 years old (85.96%) and male sex with average treatment duration of 3 days. Proportion of drug costs (33.00%) with antibiotics (14.00%) and supportive/non antibiotic drugs (19.00%). The cost of treatment is the highest cost component of all cost components in the treatment of pneumonia. Cost of treatment of pneumonia disease without co-morbidities disease between Rp. 185.808 1.248.018. Cost of treatment of pneumonia with co-morbidities disease between Rp. 249.700-501.939. The most optimal antibiotic drug used in patients without co-morbidities disease is a combination of gentamicin-amoxicillin-ceftriaxone. The most optimal antibiotic drug is used in patients with co-morbidities that are combination of cefotaxim-ceftriaxon. The cost of treatment is the highest cost component of all cost components in the treatment of pneumonia and the most optimally used antibiotic is the combination of gentamicin-amoxicillin-ceftriaxon (patient without comorbidities) and a combination of cefotaxim-ceftriaxon (patients with comorbidities).